FRANKO’S ARTISTIC DISCOURSE IN UKRAINIAN TRANSLATIONS: A LINGUACULTURAL ANALYSIS - Moskalets, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article provides a linguistic and cultural analysis of Ukrainian translations of French literature. The study reveals important aspects of the transmission of artistic symbols and cultural realia by Ukrainian translators and their influence on the perception by Ukrainian readers. The relevance of the research is due to the growing volume of translations of French texts, the importance of quality translation and the study of linguistic and cultural aspects of translation. The results of the study indicate different translation strategies used by translators to convey the content and form of the original, as well as the importance of taking into account linguistic and cultural features when reproducing artistic images. The analysis of the translation of the poem “Chanson d’automne” by Paul Verlaine emphasizes the complexity of translating poetry and the need to preserve its stylistic and sound features. ______________ References: • Hertsovska, O. Realia as a Linguistic Phenomenon. Contemporary Studies in Foreign Philology 12 (2014): 36-42. • Goodmanyan, G., Sitko, A. V., Yencheva, H. H. Introduction to Specialized Translation: Workbook for Students of Translation Specialty (Kyiv: Agrar Media Group, 2014), 257. • Hurenko, V. Specifics of Translating Socio-Political Realia. Bulletin of SumDU 1 (2007): 91-95. • Demetska, V. Equivalence and Adequacy in Reproducing Pragmatic Texts in Translation. Scientific Notes. Series "Philological Sciences (Linguistics)" 104 (1) (Kirovohrad, 2012): 35–39. • Demetska, V. Translation of Cultural Texts: Adaptation or Anti-adaptation? Teaching to Learn Translation (Sumy, 2015): 23-28. • Zorivchak, P. Realia and Translation (Based on English Translations of Ukrainian Prose) (Lviv: Publishing House of Ivan Franko National University of Lviv, 1989), 216. • Kyak, R., Naumenko, A. M., Ohui, O. D. Theory and Practice of Translation (German Language) (Vinnytsia: Nova Knyha, 2006), 592. • Yakymchuk, P. Linguacultural Communication as a Challenge for a Translator. Bulletin of Ivan Franko Zhytomyr State University 34 (2007): 217-221. • Janes, K. Translation Journal, Vol. 6 : Literary Translation (2002), Cultural Implications of Translation (bokorlang.com) (date of access: 16.09.2023). • Poèmes saturniens (1866), Poèmes saturniens (1866)/Chanson d’automne - Wikisource (date of access: 22.09.2023). • Rehail, H. Equivalence, culture et traduction. Linguistica32(2) (1992): 221–225.